Quantitative seismic-stratigraphic interpretation of the evaporite sequence in the Santos Basin. (December 2020) - Teixeira, Leonardo; Lupinacci, Wagner M.; Maul, Alexandre
Abstract: On the account of the absence of modern analogues, the interpretation of evaporite-bearing basins relies extensively on seismic and well data. Recent studies describe the intrasalt kinematic, geometries and compositions, relating the change of reflection patterns in seismic data to variations in evaporite sequences. However, these interpretations are only qualitative. This study describes a step further in proceeding from qualitative to quantitative interpretation of an evaporite-dominated interval. It integrates geophysical and geological foundations by combining rock physics, seismic inversion and statistical techniques to deliver seismic-driven facies volume of the evaporite sequence in the Santos Basin, offshore Brazil. Synthetic seismogram demonstrate the ambiguities and uncertainties in relating the seismic amplitude to salt types. Rock-physics analysis indicates that acoustic impedance is an effective differentiator of salt types in comparison to seismic amplitude. Therefore, we perform seismic inversion to transform interface property into layer property. The acoustic impedance volume mitigated significantly the risk of seismic interpretation in the salt sequence. The Bayesian classification integrates acoustic impedance and rock-physics analysis to deliver the seismic-driven facies volume, which categorizes bittern salts, halite and anhydrite. This enables the refinement of the seismic-stratigraphic interpretation of intrasalt sequences of the Ariri Formation based on the sedimentary cycles of evaporites. Additionally, we calculate proportion maps to evaluate the spatial variability of salt deposition. We observe an increase in bittern salts and anhydrite proportions from the bottom to the top of the sequence. The comparison between well-based and seismic-based proportions testifies to the quantitative potential of seismic data. The approach provides quantitative analysis of the evaporite sequence and can be applied to other salt-bearing basins. Highlights: Seismic amplitude yields highly ambiguous response to salt types. Acoustic impedance reduces interpretation errors when dealing with the intrasalt formation. We estimate the quantitative seismic classification of halite, anhydrite and bittern salts. We interpret the intrasalt stratigraphy based on cyclostratigraphy. We provide proportion maps of bittern salts and anhydrite.